Incidence and Associated Factors of Postoperative Nausea and Vomiting in Patients Undergoing Craniotomy - Pruitthithada S, Hoontanee N, Duriyaprapan P, Ittichaikulthol W (Journal of The Department of Medical Services, 2019)
Background: Intracranial surgery is a risk factor of postoperative nausea and vomiting (PONV). Previous studies showed that the incidence rates of post craniotomy PONV varied from 10% to 74%. Most of them were retrospective, or observational studies. The objective of this study is to determine the incidence and risk factors of PONV after craniotomyat Ramathibodi Hospital. Method: After ethical approval from the Ethical Clearance Committee on Human Rights Related to Researches Involving Human Subjects, the prospective study was performed. Postoperative nausea and vomiting were prospectively assessed at 1, 4, 24, 48, and 72 hours after elective craniotomy in 120 patients, 18 to 80 years old with American Society of Anesthesiologists (ASA) classifications I to IV. Patients characteristic, surgical-related, and anesthetic-related risk factors of postoperative nausea and vomiting were recorded and analyzed. Result: The overall incidence of PONV at72 hours after elective craniotomy at Ramathibodi Hospital was 35%. The history of PONV / motion sickness (adjusted RR 46.611, 95% CI 4.077-532.924, p=0.002), postoperative opioid usage (adjusted RR 9.138, 95% CI 3.063-27.259, p<0.001), blood transfusion (adjusted RR 4.886, 95% CI 1.601-14.907, p=0.005) and suboccipital craniotomy (adjusted RR 8.134, 95% CI 2.052-32.239, p=0.003) are the risk factors of PONV. The incidence of PONV is significantly lower in the patients received steroid during the perioperative period (adjusted RR 0.274, 95% CI 0.08-0.936, p=0.039). Conclusion: The cumulative incidence of PONV after craniotomy, was 35% at 72 hour. The associated risk factors were previous history of PONV/motion sickness, suboccipital surgery, blood transfusion, and postoperative opioids usage.